Variation in size distribution of juvenile pink shrimps Farfantepenaeus brasiliensis and F. paulensis in the estuarine-adjacent ocean area of Cananeia, south-eastern coast of Brazil - Salvati, Dalilla da Silva [UNESP]; Perroca, Julia Fernandes [UNESP]; Simoes, Sabrina Morilhas [UNESP]; Castilho, Antonio Leao [UNESP]; Costa, Rogerio Caetano da [UNESP] (Cambridge Univ Press, 2021)
The study characterized the structure of juveniles and sub-adults of Farfantepenaeus brasiliensis and F. paulensis in the Cananeia-Iguape estuarine lagoon system and its adjacent coastal area by evaluating the period of juvenile recruitment, sex ratio, growth, longevity, natural mortality, and development time until the late juvenile phase. Samples were collected from July 2012 to June 2014. Shrimps were identified by species and sex, and measured (carapace length - CL mm); 889 individuals of F. brasiliensis and 848 of F. paulensis were analysed. Females were more abundant than males for both species. The growth parameters of F. brasiliensis were: CL infinity = 45.5 mm, k = 1.8 year(-1) for males and CL infinity = 55.2 mm, k = 1.6 year(-1) for females; longevity of 2.52 years (males) and 2.88 years (females); and natural mortality of 1.71 (males) and 1.55 (females). For F. paulensis, the following values were observed: CL infinity = 40.7 mm, k = 2.3 year(-1) for males and CL infinity = 56.5 mm, k = 1.9 year(-1) for females; longevity of 2.04 years (males) and 2.37 years (females); and natural mortality of 2.39 (males) and 2.05 (females). The juvenile recruitment of both species peaked in January 2014. The development time until late juvenile phase was similar to 7 months (F. brasiliensis) and similar to 5 months (F. paulensis). Even though the highest abundance of juveniles did not occur in the closed season, fishing is forbidden in the estuarine area and the migration towards the adult population occurred close to or even during the closed season.
Keywords: Closed season; growth; longevity; Penaeidae; recruitment; sex ratio